Peran Guru Dalam Melaksanakan Bimbingan dan Konseling di SD Muhammadiyah 21 Baluwarti - Pratiwi, Osy Putri; , Murfiah Dewi Wulandari, S.Psi.,M.Psi Psikolog (2017)
The role of teachers influences student development. To help the students to develop well can be counseling and guidance activities, this activity is needed for students who experience problems, guidance activities can be implemented by classroom teachers during the learning process or after the learning. With the existence of guidance and counseling activities are expected to make personal students become better or can help students who have problems can be resolved. This study aims to determine the role of teachers in melaksnakan guidance and counseling on students in SD Muhammadiyah 21 Baluwarti, constraints experienced by teachers while carrying out guidance and counseling activities and solutions for teachers while carrying out guidance and counseling. The subjects of this study were 1st grade teachers to grade 6 teachers and 1 principal. Techniques of collecting data using interviews, observation and documentation. Data analysis using source triangulation. Based on the results of data analysis of research in SD Muhammadiyah 21 Baluwarti can be concluded that the role of teachers in carrying out guidance and counseling on students is good. Because teachers in SD Baluwarti 21 are in accordance with teacher role indicators in implementing guidance and counseling. So the greater the role of teachers in guidance and counseling activities then the better the achievements and attitudes of students at school or outside school. Keywords: teacher role, guidance and counseling